Simultaneous Influenza Vaccination and Hymenoptera Venom Immunotherapy Is Safe - Ewa Czerwińska; Marita Nittner-Marszalska; Robert Pawłowicz; Leszek Szenborn (Vaccines, 2021)
Allergen immunotherapy (AIT) is a standard treatment for venom allergy. Our purpose was to determine if the administration of both allergen and protective vaccines during one visit is safe and if such a procedure does not deteriorate the tolerance of both vaccines. As current guidelines are based on theoretical assumptions, our aim was to establish the safety and tolerance of shortening the recommended interval between vaccinations. During two influenza seasons, 44 adult patients, with a history of systemic allergic reactions after a Hymenoptera sting, underwent 58 simultaneous allergen and seasonal influenza vaccinations (study group) while in the maintenance phase of venom immunotherapy (VIT). The control group consisted of 57 healthy adults who were vaccinated against influenza only. The conditions of the patients were monitored during hospital visits, and via telecommunication methods to evaluate the safety and tolerance of the procedure. Within the study group, there were no immediate or delayed allergic reactions after vaccinations. The presence of common, adverse influenza vaccine reactions among study group patients (29%) and control group patients (32%) did not differ significantly (p = 0.841). We did not observe a difference in the frequency of various adverse reactions in either group or a dependence of previous vaccinations against influenza on the occurrence of adverse reactions. The most frequent occurrences were local adverse reactions. All adverse reactions were resolved without treatment. These findings demonstrate the safety and tolerance of an influenza vaccination and Hymenoptera venom immunotherapy administration during one visit.